Literature Review: Big Data dan Data Analys pada Perusahaan - Eka Mayasari; Agussalim Agussalim (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2023)
Companies worldwide have witnessed an extraordinary data revolution. Big data and data analytics have become highly valuable assets for companies, playing a crucial role in decision-making, business strategies, and competitiveness in an increasingly competitive market. This phenomenon creates a new paradigm that can transform how companies operate and interact with their customers. The objective of this research is to understand the importance of using big data and data analytics in a company. This study includes a comprehensive literature analysis and combines empirical findings from various previous studies. The method used in this research is a literature review approach. This journal is compiled based on the analysis of research findings sourced from various journals accessed through the Google Scholar database. The research results indicate that big data and data analytics have become essential elements in modern companies, helping them make more accurate decisions, improve operational efficiency, and achieve competitive advantages. However, companies must also pay attention to data privacy and security issues to ensure that their use of Big Data complies with applicable regulations.